1998
DOI: 10.1055/s-0037-1614994
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin in Human Plasma Contributes to Inhibit Fibrinolysis through Acceleration of Thrombin-dependent Activation of Plasma Procarboxypeptidase B

Abstract: SummaryThrombomodulin (TM) expressed on endothelial cells binds thrombin and initiates anticoagulant pathways. Soluble functional proteolytic fragments of TM are also present in circulating plasma. Recently, it was reported that TM accelerated thrombin-dependent plasma procarboxypeptidase B (pro-pCPB) activation in a purified system and suggested that TM may inhibit fibrinolysis in crude plasma. The aim of present study was to evaluate any functional role of soluble TM fragments in plasma or purified TM added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 25 publications
1
54
0
Order By: Relevance
“…However, several recent reports suggest that excess activation of proCPR may exacerbate a state of disseminated intravascular coagulation (DIC) resulting from a Gram-negative bacterial infection (14,15,(22)(23)(24)(25)(26)(27). Following activation by thrombin, proCPR, otherwise known as TAFI, exerts an antifibrinolytic effect by removing carboxyl-terminal lysines on fibrin, preventing plasminogen binding and activation (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several recent reports suggest that excess activation of proCPR may exacerbate a state of disseminated intravascular coagulation (DIC) resulting from a Gram-negative bacterial infection (14,15,(22)(23)(24)(25)(26)(27). Following activation by thrombin, proCPR, otherwise known as TAFI, exerts an antifibrinolytic effect by removing carboxyl-terminal lysines on fibrin, preventing plasminogen binding and activation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Following activation by thrombin, proCPR, otherwise known as TAFI, exerts an antifibrinolytic effect by removing carboxyl-terminal lysines on fibrin, preventing plasminogen binding and activation (15). On the other hand, it has been established that CPN does not remove carboxyl-terminal lysine residues from the clot surface despite the preference for lysine residues rather than arginine residues (15,26). Furthermore, according to the present study, LPS stimulation did not essentially alter CPN expression or consumption of CPN compared with proCPR following LPS injection (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that in uPA -/-mice, a potential TM/thrombin complex may affect other non-APC-dependent targets. Previous studies have demonstrated that the TM/thrombin complex regulates the rate of plasmin generation through the effects of thrombin-activated fibrinolysis inhibitor (TAFI) on both tPA and uPA (36)(37)(38)(39). In addition, the TM/thrombin interaction has been shown to directly modulate the uPA receptor (40).…”
Section: Discussionmentioning
confidence: 99%
“…For extensive activation of proCPR in plasma, thrombin and thrombomodulin complexes (T-TM) can be used (2,14). Therefore, we used ELISA to evaluate the amount of antigens detected in plasma before and after activation by T-TM.…”
mentioning
confidence: 99%